E-Learning Sebagai Media Pembelajaran Berbasis Edmodo - Rahmad Syah; Susilawati Susilawati; Eky Ermal Muttaqin (Universitas Medan Area, 2019)
Community demands on the quality of education services from time to time are increasingly high. Along with the development of increasingly rapid science and technology, educational institutions in various levels and levels of education can no longer stand by to preserve the cultural and performance capabilities of a school, but must strive to innovate changes in various aspects so that they are not left behind by people who live in in the era of globalization. Computer-based Information Technology is one medium that is quite effective in managing school academic information systems. The use of e-learning in schools as learning media can open up broad insights for students how to communicate in teaching and learning activities using computers. With the construction of e-learning systems as edmodo-based learning media can improve the quality of students in using computers. In addition, it is expected to facilitate students in taking a computer-based national examination.